The Story Behind Soap - Christin Ditchfield (Oxford, United Kingdom Capstone Global Library Ltd, 2011)
Where does the word "soap" come from? What are the active ingredients in soap? How was soap used in the Middle Ages? To uncover the hidden facts behind everyday things, explore the secrets of True Stories. True Stories reveals the surprising truth about a range of subjects. Discover everything you could wish to know, and some things you'll wish you didn't, about a huge range of topics!
Keywords: Non Fiction -- Non Fiction